Teaching and Research in Contemporary Higher Education
XXII, 410 p.
Keywords: This book discusses how teaching and research have been weighted differently in academia in 18 countries and one region, Hong Kong SAR, based on an international comparative study entitled the Changing Academic Profession (CAP). It addresses these issues using empirical evidence, the CAP data. Specifically, the focus is on how teaching and research are defined in each higher education system, how teaching and research are preferred and conducted by academics, and how academics are rewarded by their institution. Since the establishment of Berlin University in 1810, there has been controversy on teaching and research as the primary functions of universities and academics. The controversy increased when Johns Hopkins University was established in 1876 with only graduate programs, and more recently with the release of the Carnegie Foundation report Scholarship Reconsidered by Ernest L. Boyer in 1990. Since the publication of Scholarship Reconsidered in 1990, higher education scholars and policymakers began to pay attention to the details of teaching and research activities, a kind of ‘black box’ because only individual academics know how they conduct teaching and research in their own contexts.